The life and death of Theodore of Stoudios (Cambridge, Massachusetts ; London, England)
xxiv, 382 sayfa
Keywords: “The three texts contained in this volume, translated into English for the first time, commemorate the life of one of the most celebrated of Byzantine churchmen. Theodore of Stoudios (759-826) played a leading role in both monastic and political life in Byzantium. He is celebrated as a saint in the Orthodox Church, particularly for his stalwart defense of icon veneration during the period of Second Iconoclasm. He was also responsible for lasting reforms in monastic organization, widely imitated by later founders throughout the empire. The survival of much of his vast literary output-homilies, letters, verses, and hagiography-testifies to his lasting influence“ --